Fullerenes For Anticancer Drug Targeting: Teaching An Old Dog A New Trick - Dhiman, Shikha; Kaur, Amardeep; Sharma, Manu (Mini Reviews in Medicinal Chemistry, 2022)
Fullerenes are the allotropic form of carbon consisting of a cage-like structure due to which they have attained special attention from researchers since their discovery in 1985. The unique chemical and physical properties of fullerene have attracted researchers to develop a variety of its biomedical applications. The closed cage structure of fullerenes can be used for various drug delivery applications and can also act as a medium for controlled release formulations. The development of targeted anticancer drug and drug delivery systems is one of the most challenging fields, which is widely studied and researched. In this review, we aim to provide a comprehensive review on the most recent advances in fullerenes as targeted anticancer drug delivery systems along with their therapeutic applications and challenges, thus serving the pharmaceutical and biotechnology community.
Keywords: Fullerenes